2013
DOI: 10.1177/0143831x13491842
|View full text |Cite
|
Sign up to set email alerts
|

Employment protection under fire: Labour market deregulation and employment in the European Union

Abstract: Employment protections are currently being targeted by European policy makers seeking solutions to persistently high levels of unemployment and weak economic growth. This article argues that labour market deregulation is unlikely to usher in a period of renewed growth in good quality jobs. The findings point to the important role of employment protections in stemming job losses in the initial stages of the economic crisis that began in 2008, although protections have not prevented subsequent heavy job losses i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 24 publications
0
38
1
2
Order By: Relevance
“…As shown in Figure , EU countries with relatively strong employment protections, for example Germany, tended to experience less severe job losses than those with weaker protections (e.g. the UK) during the early stages of the crisis (for a fuller discussion see Heyes and Lewis, ). It is likely that constraints on dismissals served to stem job losses in the initial period and encouraged employers to look for internal means of reducing labour costs.…”
Section: The Impact Of Epl Before and During The Crisismentioning
confidence: 99%
“…As shown in Figure , EU countries with relatively strong employment protections, for example Germany, tended to experience less severe job losses than those with weaker protections (e.g. the UK) during the early stages of the crisis (for a fuller discussion see Heyes and Lewis, ). It is likely that constraints on dismissals served to stem job losses in the initial period and encouraged employers to look for internal means of reducing labour costs.…”
Section: The Impact Of Epl Before and During The Crisismentioning
confidence: 99%
“…Stricter EPL has been shown to prevent job losses in the initial stages of the economic crisis (Heyesm & Lewis, 2014). In addition, countries that maintained relatively strong employment protection experienced fewer labour-market disruptions (Heyes, 2011).…”
Section: The Matching Process: Power Resources and Institutional Buffmentioning
confidence: 99%
“…They claim that weakening the restrictions on the labour markets reduces the dismissing costs and encourages the employers to hire more workers (Heyes and Lewis, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…2 Heyes and Lewis (2013) argue that the suggestion of weakening the employment protections is not a new debate among the policy markers. Starting for 1980s the IMF and OECD have suggested that the solution to jobs growth lay in relaxing the rules in the labour markets.…”
mentioning
confidence: 99%
See 1 more Smart Citation